1980
DOI: 10.1177/0145482x8007400202
|View full text |Cite
|
Sign up to set email alerts
|

Irrational Thinking and Adjustment to Loss of Vision

Abstract: Individual differences in adjusting to or coping with blindness appear related to the presence or absence of certain irrational belief statements about this disability. As a whole, these appear to constitute much of the mythology of blindness. The statements fall into four general categories: (1) Blind people are different from sighted people in their self-worth and value; (2) Blind people have a unique psychological constitution; (3) Blind people have a special relationship with other people and society in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…In the field of visual impairments, Dodds, Ferguson, Ng, Flannigan, Hawes, and Yates () proposed that cognitive therapy and attribution retraining would be beneficial, although they did not have empirical data about its effectiveness for clients with acquired visual impairment. Needham and Ehmer () also recommended cognitive therapy, and provided useful clinical suggestions, but not an empirical outcome evaluation. Although Dodds et al. and Needham and Ehmer both recommended cognitive therapy, they suggested different targets for cognitive modification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of visual impairments, Dodds, Ferguson, Ng, Flannigan, Hawes, and Yates () proposed that cognitive therapy and attribution retraining would be beneficial, although they did not have empirical data about its effectiveness for clients with acquired visual impairment. Needham and Ehmer () also recommended cognitive therapy, and provided useful clinical suggestions, but not an empirical outcome evaluation. Although Dodds et al. and Needham and Ehmer both recommended cognitive therapy, they suggested different targets for cognitive modification.…”
mentioning
confidence: 99%
“…Needham and Ehmer () also recommended cognitive therapy, and provided useful clinical suggestions, but not an empirical outcome evaluation. Although Dodds et al. and Needham and Ehmer both recommended cognitive therapy, they suggested different targets for cognitive modification. Dodds et al. suggested modifying the cognitions that were related to the attribution of success in training, whereas Needham and Ehmer attempted to modify irrational belief statements about visual disability.…”
mentioning
confidence: 99%
“…It is important to work with the rehabilitation programme both from a cognitive and an affective perspective. Firstly, Needham and Ehmer (1980) suggested that it is important for a blind person to learn new coping skills in order to make it possible to handle different situations. Secondly, Hudson (1994) suggested that blind people should also be taught to play an active role in educating sighted individuals about the way that they, as blind people, would like to be viewed and treated.…”
Section: Discussionmentioning
confidence: 99%
“…Needham and Ehmer categorized the 16 maladjusted belief statements that visual impaired people often made into four categories [43]. These were that (1) blind people were different from sighted people in their self-worth and value (e.g., an individual's worth was dependent upon his/her physical adequacy.…”
Section: Cognitive Therapy: Maladjusted Beliefmentioning
confidence: 99%